2005
DOI: 10.1038/sj.npp.1300678
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine is not Required for the Hyperlocomotor Response to NMDA Receptor Antagonists

Abstract: N-methyl-D-aspartate (NMDA) receptor antagonists can elicit symptoms in humans that resemble those seen in schizophrenic patients. Rodents manifest locomotor and stereotypic behaviors when treated with NMDA receptor antagonists such as phencyclidine (PCP) or dizocilpine maleate (MK-801); these behaviors are usually associated with an activated dopamine system. However, recent evidence suggests that increased glutamatergic transmission mediates the effects of these NMDA receptor antagonists. The role of dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
54
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 53 publications
11
54
1
2
Order By: Relevance
“…It has therefore been suggested that blockade of NMDA receptors may lead to inhibition of the corticostriatal glutamatergic pathway and eventually result in excessive activation of cortical and subcortical structures, thereby stimulating locomotor activity (Carlsson et al, 2001). However, the different views on the neuronal substrates underlying MK-801-induced stimulation of locomotor activity are not mutually exclusive (Chartoff et al, 2005). Our immunohistochemical analyses of the NMDA-receptor subunit NR1 did not reveal any significant changes as a function of the prenatal and postnatal manipulations (Table 3).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has therefore been suggested that blockade of NMDA receptors may lead to inhibition of the corticostriatal glutamatergic pathway and eventually result in excessive activation of cortical and subcortical structures, thereby stimulating locomotor activity (Carlsson et al, 2001). However, the different views on the neuronal substrates underlying MK-801-induced stimulation of locomotor activity are not mutually exclusive (Chartoff et al, 2005). Our immunohistochemical analyses of the NMDA-receptor subunit NR1 did not reveal any significant changes as a function of the prenatal and postnatal manipulations (Table 3).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, MK-801-induced hyperlocomotor activity can also occur in the absence of endogenous dopamine (Carlsson and Carlsson, 1989;Chartoff et al, 2005). It has therefore been suggested that blockade of NMDA receptors may lead to inhibition of the corticostriatal glutamatergic pathway and eventually result in excessive activation of cortical and subcortical structures, thereby stimulating locomotor activity (Carlsson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, NMDAR antagonists induce hyperlocomotion in catecholamine-depleted animals (Carlsson and Carlsson 1989;Swanson and Schoepp 2002). PCP and MK-801 produced hyperlocomotion in genetically DA-deficient mice that was not significantly antagonized by the D 2 antagonist, haloperidol, nor the D 1 antagonist, SCH 23390 (Chartoff et al 2005). The limited importance of nucleus accumbens dopaminergic activity for NMDAR antagonistinduced locomotion is also supported by the finding that DA depletion via local administration of 6-OH-DA, attenuates, but does not prevent, PCP-induced hyperlocomotion (Steinpreis and Salamone 1993).…”
Section: Nmda Receptor Non-competitive Antagonist-induced Hyperlocomomentioning
confidence: 94%
“…The psychomotor and reinstating effects of MK-801 are thought to occur independent of dopamine release and dopamine receptor activation (Druhan et al, 1996;Wise et al, 1996;De Vries et al, 1998;Chartoff et al, 2005). Similar to D 2 receptor challenge, animals in both low and high intake groups displayed robust locomotor sensitization to MK-801 challenge following chronic cocaine self-administration.…”
Section: Brain Cocaine Levelsmentioning
confidence: 99%